Overview of Seasonal Prevalence of Liver Fluke & Rumen Fluke Infestation in Cattle and Buffalo of Western Chitwan, Nepal - Bista, S.; Lamichhane, U.; Singh, D. K.; Regmi, S. (Journal of the Institute of Agriculture and Animal Science, 2018)
Fluke infestation in domestic animals is one of the major problems of farmers in tropical condition of Chitwan. A prospective study was done in western Chitwan, Bharatpur Metropolitan City, ward 26 &16, Nepal in two different seasons-summer and winter to describe the seasonal prevalence of fluke infestation in dairy cattle and buffalo. Sedimentation technique of faecal examination was performed to recover the parasite eggs. In the study, the prevalence of fluke infestation was found to be higher in the summer (26%) than in winter (22%). Similarly, among cattle Jersey cross (39.5%) showed the highest infestation of flukes among the breeds followed by Jersey (12.5%), among the buffalo breed the rate of infestation was found higher in Murrah cross (21.4%) followed by local (20.0%). No Murrah breed in the study were positive for GI parasite. In the study carried out in 38 calf, 7 heifer and 55 mother the faecal examination for fluke egg was positive 26.3% of calves, 28.6% of heifers and 21.8% of mothers respectively. Out of 43 buffalo and 57 cattle the parasitic infestation was found in 18.6% and 28.1% of sample respectively. Although cattle were seen more susceptible to flukes, the relation was not statistically significant. The study shows that the fluke infestation may be producing subsequent production loss due to its high prevalence in dairy cattle and buffalo.